2001
DOI: 10.1038/414652a
|View full text |Cite
|
Sign up to set email alerts
|

The AAA ATPase Cdc48/p97 and its partners transport proteins from the ER into the cytosol

Abstract: In eukaryotic cells, incorrectly folded proteins in the endoplasmic reticulum (ER) are exported into the cytosol and degraded by the proteasome. This pathway is co-opted by some viruses. For example, the US11 protein of the human cytomegalovirus targets the major histocompatibility complex class I heavy chain for cytosolic degradation. How proteins are extracted from the ER membrane is unknown. In bacteria and mitochondria, members of the AAA ATPase family are involved in extracting and degrading membrane prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
970
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,030 publications
(999 citation statements)
references
References 30 publications
26
970
1
2
Order By: Relevance
“…To determine whether Evi is an endogenous ERAD substrate, we silenced the expression of several known ERAD components and monitored changes in Evi abundance. The AAA‐ATPase VCP is an essential component of ERAD processing by promoting the dislocation of ERAD substrates across the ER membrane into the cytosol to allow proteasomal degradation (Ye et al , 2001; Fig 4A). Knockdown of VCP by both pooled and single siRNAs stabilized endogenous Evi protein without affecting its mRNA levels (Figs 4B and EV3E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether Evi is an endogenous ERAD substrate, we silenced the expression of several known ERAD components and monitored changes in Evi abundance. The AAA‐ATPase VCP is an essential component of ERAD processing by promoting the dislocation of ERAD substrates across the ER membrane into the cytosol to allow proteasomal degradation (Ye et al , 2001; Fig 4A). Knockdown of VCP by both pooled and single siRNAs stabilized endogenous Evi protein without affecting its mRNA levels (Figs 4B and EV3E).…”
Section: Resultsmentioning
confidence: 99%
“…ERAD is a specialized ubiquitin‐proteasome system (UPS)‐dependent process that prevents the secretion and aggregation of proteins that failed to fold or assemble appropriately (Vembar & Brodsky, 2008). Following coordinated recognition and delivery to membrane‐embedded ubiquitination machineries, ERAD substrates are retrotranslocated across the ER membrane into the cytosol through the AAA‐ATPase VCP (also known as p97) and degraded by 26S proteasomes (Ye et al , 2001; Vembar & Brodsky, 2008; Smith et al , 2011; Olzmann et al , 2015). Since ERAD‐dependent quality control has been linked to a range of cellular processes and human diseases (Zettl et al , 2011; Guerriero & Brodsky, 2012; Perrody et al , 2016), understanding its molecular mechanisms is an important step to develop potential treatment strategies (Tsai & Weissman, 2010; Hetz et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…76,77 Ubiquitination machinery similar to that of yeast is also employed, and a homolog of Cdc48p, termed p97, has been shown to cooperate with mammalian homologs of Ufd1p and Npl4p in substrate dislocation. [78][79][80] Recently, two groups using independent functional criteria identified Derlin1 as a mammalian homolog of Der1p and demonstrated that it mediates the association of p97 with the ER membrane to facilitate ERAD. 81,82 Another protein in this p97 targeting complex, VIMP, was also identified in one of these studies.…”
Section: Esr In Mammalsmentioning
confidence: 99%
“…The structure retains its symmetry and rigidity until all ATP molecules are hydrolyzed, at which point HP0525 can return to its nucleotide free form. Although sequence-unrelated, the structure of HP0525 is remarkably similar to that of the p97 AAA ATPase which, similarly to the related Nethylmaleimide-sensitive fusion protein (NSF), plays a central role in organelle assembly and membrane fusion processes in the endoplasmic reticulum and the Golgi apparatus (Patel and Latterich, 1998;Ye et al, 2001). It has therefore been proposed that VirB11-like proteins, by analogy to p97 and NSF, could serve as mechanical transducers providing the necessary mechanical force for the recruitment/assembly/disassembly of type IV secretion protein components, making them available for insertion into the nascent secretion apparatus and/or to facilitate substrate translocation across the inner membrane (Savvides et al, 2003).…”
Section: Virb11: a Ring-shaped Cytoplasmic Ntpase Fuelling The Secretmentioning
confidence: 99%